Accelerating the net zero transition in Asia and the Pacific: Low-carbon hydrogen for industrial decarbonization - Meng Yuan; Chunying Liu; Bohong Wang; Wenlong Shang; Haoran Zhang (Asian Development Bank Institute (ADBI), 2023)
Hydrogen is regarded as one of the limited options for decarbonizing the hard-to-abate industrial sector. This work investigates the status and potential of green and blue hydrogen in some major industrial sectors, including oil refining, chemical production, iron and steel production, and high-temperature heat applications. The focus is put on the Asia and the Pacific (APAC) region, which accounts for half of the global industrial hydrogen demand. The status of the hydrogen market, the deployment actions of low-carbon hydrogen in industrial sectors in terms of national strategies, demonstration projects, and the regional hydrogen market of the APAC countries are summarized and analyzed. Perspectives are provided in support of accelerating the further decarbonization of the industrial sector in the APAC region with low-carbon hydrogen. Despite variations across countries in APAC in terms of low-carbon hydrogen production and application potentials due to different resource endowments, energy structures, and industrial structures, the region enjoys high potential overall, and in the ability for cross-border hydrogen trading in particular.
Keywords: Q40; 330; green hydrogen; blue hydrogen; industry decarbonization; Asia and the Pacific; renewable energy